Social determinants of health protocol adherence among adults during COVID-19 pandemic in Yogyakarta, Indonesia - Supriyati, Supriyati; Baiquni, Fahmi; Siswati, Tri; Widyawati, Herni Endah; Rahmawati, Riadini; Wardani, Ratri Kusuma (Malaysian Medical Association, 2022)
Introduction: Coronavirus disease (COVID-19) must be controlled by involving all stakeholders, including the community. Community protocol compliance with COVID-19 health guidelines is essential. This study assessed the social determinants of health on community protocol compliance with COVID-19 health guidelines among adults in Yogyakarta, Indonesia. Materials and Methods: This study was a mixed-method study of 461 adults from February through May 2021 in Yogyakarta Province. We collected data through an online survey, focus group discussions, and in-depth interviews. Logistic regression was used to analyze the results. Results: Most respondents (86) always wore masks, followed social distancing (51.8), and washed their hands regularly (99). Subjects older than 45 years, women, and community leaders demonstrated greater compliance with COVID-19 health protocols compared to other people. On the other hand, the occupation has become a healthy lifestyle practice indicator. Conclusion: Gender, age, educational level, economics, and social status were determinants of health protocol adherence among adults in Yogyakarta. Therefore, health providers need to consider social determinants for health promotion approaches and COVID-19 prevention and control strategies. © 2022, Malaysian Medical Association. All rights reserved.